A Higher Form of Hermeneutics?: The Digital Humanities in Political Historiography - Beyen, Marnix (BMGN - Low Countries Historical Review, 2013)
Rens Bod’s optimism with regard to digital research tools also seems to be justified for the field of political history. In particular, these tools will enable us to ask questions that were hitherto unthinkable, and try to answer them on an unenvisaged scale. Unlike that which Bod suggests, however, this development will not bring us closer to revealing some alleged universal patterns in history and therefore herald a new era of Positivism. On the contrary, the digital research tools will show us manifold differences, both diachronic and synchronic, in the way (groups of) political actors identified themselves and gave meaning to the world surrounding them. Moreover, they will enable us to relate these differences to a broad range of social variables. If we really want to test the validity of these relationships however, we will have to actually interpret the texts and read them hermeneutically in their precise historical contexts. This article is part of the forum ’The End of the Humanities 1.0’.